Determination and evaluation of railway aggregate sub-ballast gradation and other properties variation - Navikas, Deividas; Bulevičius, Matas; Sivilevičius, Henrikas (Journal of Civil Engineering and Management, 2016)
The use of high quality aggregate mixture, proper technological parameters of laying and compacting as well as the required thickness of the mixture ensures railway sub-ballast layer properties. In this paper gradation, density and water permeability of 49 produced random samples of aggregate sub-ballast (ASB) mixture which were taken from the stockpile in the plant and from the uncompacted railway layer are investigated. The statistical parameters of the ASB mixture quality indicators and histograms with theoretical curves of normal distribution are presented as well. Their conformity to normal distribution was tested through the use of skewness, kurtosis, Pearson, Shapiro-Wilk and Kolmogorov-Smirnov methods. Regression analysis was employed to determine the dependence of standard deviation of percent passing on the mean percent passing through the sieves. In this paper a new method of determining the homogeneity of ASB according to the variation of gradation using the maximum standard deviation value of this dependence was employed. The minimum size n was calculated with the permissible relative error of 5%, 10%, 15% and 20%. The obtained research findings revealed that due to segregation processes the homogeneity of ASB mixture from the point of its production to application has decreased by about 38%.First published online: 20 Apr 2016